POSITION OF ‘IDDAH IN DIVORCE QABLA AL-DUKHÛL: A COMPARATIVE STUDY OF ISLAMIC FAMILY LAW REFORM IN INDONESIA AND BRUNEI DARUSSALAM - Nabilah Falah (Sahaja: Journal Sharia and Humanities, 2025)
This study aims to compare the provisions of ‘iddah qabla al-dukhûl (waiting period before the consummation of marriage) in the perspectives of Indonesian and Brunei Darussalam law. The research is of a normative juridical type with a comparative approach, using secondary data in the form of regulations analyzed qualitatively. Based on the analysis, it is found that in Indonesia, the provisions of ‘iddah are regulated in the Compilation of Islamic Law (KHI), which does not require ‘iddah for women who divorce before physical relations occur. Meanwhile, in Brunei Darussalam, which adheres to Sharia law, ‘iddah is required even if the divorce occurs before sexual intercourse, with the provision that remarriage is prohibited without the permission of a Sharia judge. These differences are influenced by social, cultural, and local customary law factors in determining Islamic family law provisions.